Дослідження процесу тепловиділення в рициновій олії з різним питомим опором під дією електричного поля - Діденко, О. В. (My University, 2021)
UK: Робота присвячена проблемі, яка виникає при процесі очищення рицинової олії в електричному полі, а саме визначенню кількості тепла, яке виділяється в електродному просторі. За допомогою комп’ютерного моделювання «ЕLCUT» представлено результати дослідження енергетичних показників, таких як тепловиділення в міжелектродному просторі багатоелектродної системи, яка використовується при очищенні рицинової олії в електричному полі при значеннях питомого опору рицинової олії 1 ˑ108 Ом/м, 1 ˑ107 Ом/м та 0,5 ˑ107 Ом/м. Отримані показники процесу тепловиділення порівняно з результатами експериментальних досліджень. EN: The work is devoted to the problem that arises in the process of processing castor oil, namely, the calculation of the amount of heat that is released in the electrode space of the electrode system. In technologies for the purification of dielectric liquids in a high-voltage electric field, the principle of action is the effect of an electric field on impurities, which, under the action of field forces, move to the surface of the liquid. Тhe paper presents the results of the study of the electrical properties of the emulsion "water in castor oil" are presented, which allow to substantiate the technology of purification of castor oil from vegetable impurities and water in an electric field. One of the conditions for the stable course of the cleaning process is the heating of the liquid. For the development of an electric field, there are many methods. The electrical conductivity of the electric field of the plane-parallel plates can be secured according to the geometrical parameters (even and the width of the plates and the thickness of the plates) in case of unchecked edge effects, as the dimensions of the plates move into them. Calculation of heat release in the electrode system of cylindrical electrodes is presented using computer simulation "ELCUT". The results of the study of energy indicators, such as heat release in the interelectrode space of a multi-electrode system, which is used when refining castor oil in an electric field at values of the specific resistance of castor oil 1 ˑ108 Ohm / m, 1 ˑ107 Ohm / m and 0,5 ˑ107 Ohm / m. The obtained indicators of the heat release process were compared with the results of experimental studies. RU: Работа посвящена проблеме, которая возникает при процессе очистки касторового масла в электрическом поле, а именно определения количества тепла, которое выделяется в электродном пространстве. С помощью компьютерного моделирования «ЕLCUT» представлены результаты исследования энергетических показателей, таких как тепловыделение в междуэлектродном пространстве многоэлектродной системы, которая используется при очистке касторового масла в электрическом поле при значениях удельного сопротивления касторового масла 1 ˑ108 Ом/м, 1 ˑ107 Ом/м и 0,5 ˑ107 Ом/м. Полученные показатели процесса тепловыделения были сравнены с результатами экспериментальных исследований.
Study of heat release in castor oil with different resistance under the action of an electric field
Исследование процесса тепловыделения в касторовом масле с различным удельным сопротивлением под действием электрического поля
Keywords: тепловиділення; рицинова олія; електрофізичні властивості; питомий опір; вода; рослинні домішки; температура; heat release; castor oil; electrophysical properties; resistivity; water; plant impurities; temperature; heat release; тепловыделение; касторовое масло; электрофизические свойства; удельное сопротивление; вода; растительные примеси; температура